Exploring the Zimbabwean Technical and Vocational Education Journey: Challenges and Prospects - Albert Mufanechiya; Bekithemba Dube; Gift Masengwe (E-Journal of Humanities, Arts and Social Sciences)
The study explored the challenges that militate against the successful implementation of Technical Vocational Education and Training (TVET) in Zimbabwe. The study gave an informed focus on biases and perceptions associated with the academic curriculum. In addressing these challenges, it becomes possible to create an environment where TVET education is valued and considered a viable pathway for individuals, and national economic and social development. Using critical discourse analysis, the study examined the perceptions of instructors and students about TVET education and identified historical factors that continue to contribute to the devaluation of TVET. The study findings revealed that the historical undervaluing of TVET subjects in comparison with academic subjects was borrowed from the colonial bottleneck education system that favoured university education over technical skills and persists today. The study underscored the need for a paradigm shift to TVET skills if economic development is to be realised in Zimbabwe. This study recommends the need to re-evaluate the status of TVET education given its contribution to the job market. This study understands the historical roots of biases against TVET and provides insights for the reconstruction of an effective TVET system in Zimbabwe that contributes toward ongoing discourses on the importance of technical skills for national development. The study recommends the need to reshape public perceptions around TVET which requires a concerted effort and long-term commitment to changing societal attitudes toward technical-vocational education.